Challenges Encountered by Ninth Grade Students in Learning the Present Perfect Tense - Maisari, Linda; Prichatin (Lexeme : Journal of Linguistics and Applied Linguistics, 2024)
This study aims to describe and analyze the difficulties faced by ninth grade students at SMPN 23 Tangerang Selatan Junior High School Ciputat in learning the present perfect tense. The sample consists of 31 ninth grade students. Employing a case study method, data were collected through observation, tests, and questionnaires, and analyzed using qualitative methods to identify common patterns and specific areas of difficulty. Findings reveal that students struggle with mastering the form of the present perfect tense, including the use of "have/has" and the regular and irregular verb forms of past participles. Additionally, students experience confusion with the time expressions associated with the present perfect tense. Recommendations include that teachers provide clear explanations and additional exercises on the present perfect tense, while students should engage in individual study and pay close attention to teachers' explanations to enhance their understanding.